At the Epicenter of COVID-19–the Tragic Failure of the Global Supply Chain for Medical Supplies - Bhaskar, Sonu; Tan, Jeremy; Bogers, Marcel L. A. M.; Minssen, Timo; Badaruddin, Hishamuddin; Israeli-Korn, Simon; Chesbrough, Henry (Frontiers in Public Health, 2020)
The tragic failure of the global supply chain in the face of the current coronavirus outbreak has caused acute shortages of essential frontline medical devices and personal protective equipment, crushing fear among frontline health workers and causing fundamental concerns about the sustainability of the health system. Much more coordination, integration, and management of global supply chains will be needed to mitigate the impact of the pandemics. This article describes the pressing need to revisit the governance and resilience of the supply chains that amplified the crisis at pandemic scale. We propose a model that profiles critical stockpiles and improves production efficiency through new technologies such as advanced analytics and blockchain. A new governance system that supports intervention by public-health authorities during critical emergencies is central to our recommendation, both in the face of the current crisis and to be better prepared for potential future crises. These reinforcements offer the potential to minimize the compromise of our healthcare workers and health systems due to infection exposure and build capacity toward preparedness and action for a future outbreak.